Circulating Queerness : Before the Gay and Lesbian Novel - Hurley, Natasha (Book collections on Project MUSE., 2018)
"Challenging the narrative that the gay and lesbian novel came into view in response to the emergence of homosexuality as a concept, Natasha Hurley posits a much longer history of this novelistic genre. She revises our understanding of the history of sexuality, as well as of the processes of producing new concepts and the evolution of new categories of language"--